Cambios radiculares analizados con morfometría digital en incisivos superiores de pacientes jóvenes durante dieciocho meses de tratamiento Ortodóncico (2008)
ABSTRACT: Orthodontically induced external root resorption is not a well understood phenomenon, and although it has been widely studied in the orthodontic literature, its nature, causes and effects are still controversial. Since there is no clarity about the apical root changes that take place during the orthodontic treatment, the aim of this study was to determine quantitative changes in root morphology during fixed periods of time (0, 6, 12, 18 months) based on a radiographic assessment. Methods: the dependent variables analysed were: area and root length, the independent variables were. treatment time, gender, age, root form, type of wire, diagnosis, oral habits, trauma, extractions, medical history, maxillary expansion and use of elastics. The method used to evaluate and calculate the root changes was the digital morphometric analysis of periapical radiographs. The sample consisted of 26 young patients (14 males- 12 females) between 11-21 years of age that were going to be treated at the Dental School of the University of Antioquia by students of the postgraduate Orthodontic program. Results and conclusions: the results had a statistical significance of 95% and led to the following conclusions: 1) root integrity was affected in the upper incisors of all patients during the 18 months of treatment. 2) The greatest changes occurred during the first six months and were significant after 18 months of treatment. 3) Upper lateral incisors were more susceptible to root resorption than upper central incisors. 4) The conditions that favored root resorption in this sample were: male gender, medical history of respiratory allergies, maxillary expansion prior to orthodontic therapy, orthodontic treatment with extractions of first upper bicuspids, and standard edgewise brackets. 5) These results are applicable to the sample analyzed and should not be extrapolated to the general population, but the information is valid to be considered in future studies with a larger sample.